Two new species of Boesenbergia (Zingiberaceae) from Palawan, Philippines - Docot R.V.A.; Santiago L.C.P; Funakoshi H; Lam, Nyee Fan (Cambridge University Press, 2020)
Recent botanical explorations in the province of Palawan, Philippines, have resulted in the discovery of two new ginger species, namely Boesenbergia eburnea Docot and Boesenbergia leonardocoi Funak. & Docot, which are described and illustrated here, including information on their distribution, habitat, phenology, ecology and conservation status. Additionally, a key to Boesenbergia species in the Philippines is provided. © Trustees of the Royal Botanic Garden Edinburgh (2020).